Employee control and work pace while working compressed work schedules in long-term care: a sequential mixed method study - Andreas Lillebråten; Anders Underthun; Daniele Evelin Alves; Vilde Hoff Bernstrøm (BMC Health Services Research, 2026)
Abstract Background In Compressed Work Schedules (CWS), employees work extended shifts in exchange for fewer workdays. While shift work is often associated with poorer psychosocial working conditions, little is known about how CWS compares with traditional shift schedules. This study examines whether and why employees working CWS experience differences in two key aspects of the psychosocial work environment: job control and work pace. Methods We used a sequential mixed-methods design. First, we conducted 39 interviews with long-term care workers, followed by a survey of 53,620 Norwegian health care union members, yielding 7,168 valid responses. Results Employees working extended day shifts within CWS reported higher job control and a lower work pace than those on traditional two- or three-shift rotations. In interviews, employees described how CWS enhanced job control by enabling them to reschedule tasks within shifts and across workdays, which in turn allowed them to slow their work pace. CWS also eliminated handovers and related disruptions, further contributing to a lower work pace. Conclusions This study found that employees working extended day shifts within CWS had higher job control and a lower work pace compared with those working traditional two- or three-shift rotations. While shift work is often associated with poorer psychosocial working conditions, our findings emphasize that how shift work is organized plays a crucial role. The interviews further highlighted that type of shift schedule can shape the psychosocial work environment by influencing both job resources and job demands. Clinical trial number Not applicable.